2009
DOI: 10.1177/0022219409345017
|View full text |Cite
|
Sign up to set email alerts
|

Passageless Comprehension on the Nelson-Denny Reading Test: Well Above Chance for University Students

Abstract: The comprehension section of the Nelson-Denny Reading Test (NDRT) is widely used to assess the reading comprehension skills of adolescents and adults in the United States. In this study, the authors explored the content validity of the NDRT Comprehension Test (Forms G and H) by asking university students (with and without at-risk status for learning disorders) to answer the multiple-choice comprehension questions without reading the passages. Overall accuracy rates were well above chance for both NDRT forms an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
33
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 6 publications
6
33
0
2
Order By: Relevance
“…Pyrczak (1974) reported a substantial amount of passage independence in multiple-choice questions related to the identification of the main idea of singular paragraphs in a sample of graduate students and in a sample of high school students. Coleman et al (2010) reported, as previously mentioned, that examinees answered above chance levels literal comprehension items as well as interpretative comprehension items. To minimize at least the successful use of different test taking strategies while answering multiple-choice items, different authors proposed guidelines for item writers (e.g., Haladyna, 2004).…”
supporting
confidence: 62%
See 3 more Smart Citations
“…Pyrczak (1974) reported a substantial amount of passage independence in multiple-choice questions related to the identification of the main idea of singular paragraphs in a sample of graduate students and in a sample of high school students. Coleman et al (2010) reported, as previously mentioned, that examinees answered above chance levels literal comprehension items as well as interpretative comprehension items. To minimize at least the successful use of different test taking strategies while answering multiple-choice items, different authors proposed guidelines for item writers (e.g., Haladyna, 2004).…”
supporting
confidence: 62%
“…Research has provided evidence for the so-called "passage-independence, that is, the likelihood that on some items, an examinee could respond correctly : : : without having read the accompanying passage" (Coleman, Lindstrom, Nelson, Lindstrom, & Gregg, 2010, p. 244). Consequentially, there is a long history of criticism on multiple-choice reading comprehension test items as well (e.g., Coleman et al, 2010;Drum et al, 1981;Katz, Blackburn, & Lautenschlager, 1991;Katz, Lautenschlager, Blackburn, & Harris, 1990;Katz, Marsh, Johnson, & Pohl, 2001;Keenan & Betjemann, 2006;Lifson, Scruggs, & Bennion, 1984;Powers & Leung, 1995;Preston, 1964;Pyrczak, 1972Pyrczak, , 1974Pyrczak, , 1976Rost & Sparfeldt, 2007;Samuels, 1968;Tian, 2006;Tuinman, 1973Tuinman, -1974. Katz et al (1990, Experiment 1), for example, administered 100 multiple-choice reading comprehension test items stemming from the verbal reasoning task of the Scholastic Aptitude Test (SAT) without presenting the corresponding text passages to college students.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Apesar de o teste possuir bons indicadores psicométricos, tem-se apontado problemas relacionados à validade (p. ex., Coleman, Lindstrom, Nelson, Lindstrom, & Gregg, 2010) e precisão (Murray-Ward, 1998.…”
Section: Instrumentos De Medidas Internacionaisunclassified